Role of Neutrophils in Systemic Vasculitides - Michailidou, Despina; Mustelin, Tomas; Lood, Christian (Frontiers in Immunology, 2020)
Neutrophils and neutrophil extracellular traps (NETs) contribute to the pathogenesis of many autoimmune diseases, including vasculitis. Though neutrophils, and NETs, are known autoantigens in anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis, promoting disease progression, the role of neutrophils and NETs in large vessel vasculitis, including giant cell arteritis (GCA), is not well understood. In this review, we summarize the current insight into molecular mechanisms contributing to neutrophil-mediated pathology in small and medium vessel vasculitis, as well as provide potential translational perspectives on how neutrophils, and NETs, may partake in large vessel vasculitis, a rare disease entity of unclear pathogenesis.